Cognitive architecture and the learning of language knowledge. (October 2015) - Waters, Alan
Abstract: In a recent study of trends in language teaching pedagogy, I identified a major professional dichotomy regarding preferred approaches to the teaching of 'language knowledge'. In general, it was shown that the theoretical discourse of language teaching favoured a 'communicating-to-learn' approach in the matter (e.g., task-based learning), whereas the practitioner 'world' leaned more towards a 'learning-to-communicate' approach (e.g., Presentation–Practice–Production). The purpose of this paper is to build on these findings by attempting to determine to what extent either of these pedagogic stances can be justified. In doing so, recent research and theorising on the workings of memory in relation to the learning of factual information is reviewed. On the basis of the characteristics of cognitive architecture that this literature describes, it is taken to indicate that i), long-term memorisation of knowledge is the key to skilled performance, and ii), guided or 'direct' instruction is superior to problem-solving or discovery-oriented forms of pedagogy in facilitating the long-term learning of factual information. Following this, the implications of these findings for language teaching pedagogy are discussed. In particular, they are seen to provide a rationale for current professional perspectives concerning the teaching of language knowledge to be re-conceptualised.